Pengembangan Kawasan Riverfront di Sungai Banjir Kanal Timur Kota Semarang dengan Konsep Eco-Riverwalk Village (Studi Kasus : Kelurahan Mlatiharjo, Kecamatan Semarang Timur) - M.H. Subianto; P. Prayogo; R.D. Gustina; A. Syahrani; D.A. Sihaloho; R. Nurrokhmi; R.J. Royson; T.R. Debby; L. Haulah; D.O. Hapsari; R. Syahlisben (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Semarang city has two canals which was developed to decrease the flood risk happened since 19th century, those are known as Banjir Kanal Timur (BKT) and Banjir Kanal Barat (BKB). Both canals which are made connected to Sungai Garang are served as primary drainages that flow directly to the sea. The weak regulation of limitation zone (e.g. riverfront) caused many violations done by people around the area by built houses or places for working along BKT riverfront. Many buildings are made as houses (i.e. commonly used by the poor) drives domestic waste dumped in the river. This is one of many driving forces caused flooding in Semarang City (i.e. the nature factor is erosion happen in BKT river upstream). Those problems caused sedimentation in BKT downstream and indirectly caused the water spilled to the settlement around the river. The development by Eco-Riverwalk Village Concept are implemanted as an effort to improve the ecology aspect in riverfront area by build a linear park as a new identity of Kelurahan Mlatiharjo Riverfront. Linear park is the implemantation of ‘riverwalk’ concept (i.e. the walkable zone along the river) and improve the aesthetic value in case study area.